Analisis Karakter Tertanggung oleh Pemegang Polis Perusahaan Asuransi Swasta di Indonesia dengan Metode Rough Set - Ameilea Chealsea Ekaputrie; Achmad Fauzan (EKSAKTA: Journal of Sciences and Data Analysis, 2023)
Insurance provides services in the form of services in facilitating a disaster that may occur based on a history of problems that have occurred. One of the private insurance companies in Indonesia has provided an insurance service program to guarantee employee welfare for policy-holding companies. The purpose of this research is to find out the pattern of association rules from the character of the insured by the policyholder so that it is expected to be able to make valuable information as input or consideration for the policymakers of private insurance companies in Indonesia. This study uses the rough set method as one of the efficient data analysis methods or techniques in database mining or knowledge discovery in relational databases. Rough sets provide algorithms to quickly and easily find hidden patterns in data. The results of the pattern of association rules for the character of the insured by the policyholder have formed as many as 14 rules. The certainty value is intended as a proportionate evaluation amount in order to find out the record of insurance claims that can be chosen by the insured. At the same time, the coverage value is intended as an evaluation amount to produce a decision for the insured to submit a claim record. The probable percentage of all events that are most recommended is seen from the highest coverage value related to record indicators, namely for administration by 45.9%, inspection by 44.1%, others by 40.8%, operation by 48.8%, financing by 46.3%, maintenance by 42%, and compensation of 65.9%.